Is this a good time to invest in Panamax tankers? - Lim, Daryl Sze Hng. (2012)
This paper aims to mainly analyse the newbuilding Panamax tanker market, with the 5-year old secondhand Panamax tanker market also considered in this paper as an alternative investment option, so that a recommendation can be made to potential investors whether they should invest into either of these markets at the current point in time. The paper carried out historical trend analyses and evaluated the current supply and demand of Panamax tankers in the market. Also, a segment on trend indicators was analysed using the correlation coefficient method together with scatter diagrams to derive patterns between the decision to invest into a Panamax tanker and the chosen variables. A discounted cash flow analysis was done for a newbuilding as well as a 5-year old secondhand Panamax tanker to find the net present value worth of each type of investment. Finally, a qualitative analysis was carried out on 2 different types of ship investors through the use of interviews to obtain insights into the fundamental strategies of these investors, thereby establishing their particular risk profiles, where after an investment decision was recommended to them.